NEW ASPECTS OF SEDIMENTATIONAL DETERMINATION OF MASTICATORY EFFICIENCY - Korol, D.M.; Kalashnikov, D.V.; Kindiy, D.D.; Toncheva, K.D.; Zaporozhchenko, I.V. (World of Medicine and Biology, 2017)
Based on the consideration of actual masticatory eficiency as one of the key criteria of dental rehabilitation success the authors of the given article aimed at the development of their own masticatory test procedure which features the determination of the indicators of agar chopping and grinding. The experimental group comprised 95 volunteers whose task was to chop the offered patterns with the help of 10 masticatory movements in the free mode. Volunteers were involved into research on the basis of such criteria as intact dentitions and physiological occlusion. Their chopped fragments were collected and 95 digital images were acquired to be analysed with the help of specifically developed by authors plugin for the software ImageJ. The prospects of the further studies the authors see in the uses of the received results to determine the conditional norm and compare it with the indices acquired from the patients of different groups with malocclusion. The other application of these findings is possible assessment of the dynamics and results of orthopedic rehabilitation.
Keywords: chewing; masticatory efficiency; masticatory test patterns; index of chewing efficiency